Implementasi Algoritma Haversine Formula Pada Aplikasi Sadewa (Sistem Informasi Destinasi Wisata) Kota Salatiga Berbasis Android - Rohmatulloh, Yusuf Ma’iin; Herlambang, Bambang Agus; Wibowo, Setyoningsih (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
Abstract - Salatiga is a city in Central Java Province which is located in the middle of two big cities, namely Semarang City whichÂ areÂ 49 km away andÂ SurakartaÂ City which is 52 km away. DuringÂ the colonialism, the Dutch government dubbedÂ SalatigaÂ as "DeÂ SchoonsteÂ StadÂ van Midderi-Javaborder" or the most beautiful city in Central Java. At this time the government of Salatiga City is working to make Salatiga again the most beautiful city in Central Java by making development efforts to beautify the city. To support this program,Â an informationÂ technology is needed to improve information about tourism. Tourists who will visitÂ to needÂ information on the nearest tourist destination to plan a trip to a tourist destination. The search for the nearest location can be applied using one of the algorithms, namely theÂ HaversineÂ Formula algorithm. This study uses Google Maps to display location routes. In terms ofÂ a utilization, it is hoped that this information system can make it easier for tourists to visit tourist destinations inÂ SalatigaÂ City.